(untitled) (Fiep Bulletin - online, 2012)
Postural control is the process by which the central nervous system, based on information coming from sensory systems of visual, vestibular and somatosensory systems, create references to develop the best strategy for maintaining balance, producing patterns of muscle activity to the appropriate relationship between the center and the mass base of support. Objective: The objective is to evaluate since postural control in seniors through stabilometry, associated with motor and cognitive dual task under conditions open and closed eyes. Methods: The sample consisted of 12 volunteers, over 65 years, of both sexes, healthy. The subjects were evaluated on a force platform under the following conditions: simple task - remain standing stable, dual-motor task - remain stable foot holding a plastic cup almost full of water; cognitive dual task - to remain stable standing talking aloud day of the week in reverse. In the eyes open and closed conditions. We analyzed the area of the ellipse 95% of the points and the average speed of center of pressure. Results: Data showed that balance changed in the dual task condition eyes open and dual cognitive task showed higher levels of instability in the eyes closed condition. Conclusion: The increased postural demands in the double reveal a greater influence on the balance of cognition.